On some encrusting Xeniidae (Octocorallia): Re-examination of the type material of Sansibia flava (May, 1898) and a description of new taxa - Benayahu, Yehuda; Ekins, Merrick; Ofwegen, Leen P. Van; Samimi-Namin, Kaveh; Mcfadden, Catherine S. (Zootaxa, 2022)
The type of the xeniid soft coral Sansibia flava (May, 1898) is re-described for the first time and its morphological diagnosis is presented. A subsequent integrated analysis of molecular and morphological characters of related Xeniidae, including species indigenous to the Indo-Pacific Ocean and invasive in the Atlantic (Brazil), led to the description of a new Sansibia species, as well as two new genera comprising an additional three new species. All of these taxa are encrusting, with polyps arising directly from a spreading basal membrane. Molecular phylogenetic analyses show that these genera are not sister taxa, thus further emphasizing the remarkable phylogenetic diversity of xeniids with such a growth form. The sclerites of all species are uniformly ellipsoid platelets, abundant throughout the colony. The species exhibit restricted, non-overlapping geographic ranges, with distinct genotypes (molecular operational taxonomic units) found in different marine realms. The results emphasize the importance of re-examination of original old type material while applying molecular phylogenetic analyses in order to delineate species boundaries and to recognize biodiversity patterns.